Analisis Manajemen Risiko Kesehatan dan Keselamatan Kerja di Bagian Filing RSUP dr. Soeradji Tirtonegoro Klaten - Novia Zahroh; Andri Permana Wicaksono; Atma Deharja (Politeknik Negeri Jember, 2020)
Medical records storage is an activity to protect the medical records from the physical damage and the contentof the medical records. Medical records storage process has risks that can threatening the occupational safetyand health of medical records staff. One of the efforts in occupational safety and health is by giving protectionfor the medical records staff by using personal protective equipment. At filing RSUP dr. Soeradji TirtonegoroKlaten found a problem that employees do not use personal protective equipment such as masks andhandscoon, the roll o’pack high is not ergonomic and it does not have Standart Prosedure Operational. Thenurse has risk to experience musculosveletal disorders, hands are itchy, sneeze, scraped paper or sharpmedical record map, and has strangulated the roll o’pack when they do the job. The purpose of this researchwas to analyzed the Health Management risk and Occupational Safety in ifiling RSUP dr. Soeradji TirtonegoroKlaten. Type of qualitative research. Some employees in filing used as Respondents. The results of thisresearch were 16,6% low risk, 50 % moderat risk, and 33,4% in high risk. Based on this results the controlefforts was redesign the map folders material, regulated the high of roll o pack, provided the vacuum cleaner,had encouraged the officers to always washed their hands after touched the medical records, made theStandart Prosedure Operational for occupational safety and health in filing, and gave a punishment ifemployees did not used personal protective equipment.